Performance Analysis of Sugar Production in Ngadirejo Sugar Factory - Husna, Afifa; Nuriza Putri, Desiana; Alamudin Manshur, Hanif (JURNAL AGROINDUSTRI HALAL, 2023)
The Ngadirejo Sugar Factory (PG) in Kras District, Kediri Regency is one of the business units whose productivity ranks second highest among the 9 PG subsidiaries of PT. Perkebunan Nusantara (PTPN) X, which reached 6,250 tons of sugar cane per day. With this high productivity, the quality of sap must always be maintained. This study aims to determine the performance of PG Ngadirejo sugar production from the aspect of raw sap, namely from the solution color value (ICUMSA), %brix, %pol, reducing sugar value, and pH to produce high-quality white crystalline sugar as well. Sap quality data from the quality assurance (QA) section of PG Ngadirejo for five days were taken and analyzed descriptively on the performance of the factory based on these parameters. %brix performance value; %pol; reducing sugar; pH; yield; ICUMSA; BJB; and the moisture content is 64 °Brix, respectively; 46 %; 6.2%; 5; 6-7%; 168.86-179.86 IU; 1.010 mm; and 0.02%. Based on the results obtained, the value of %brix, %pol, reducing sugar, ICUMSA, BJB, and water content have met the standards set by SNI. However, what needs to be improved is the yield value of white crystal sugar produced for 5 days which is still below the average value.